Noniterative density functional response approach: application to nonlinear optical properties of p-nitroaniline and its methyl-substituted derivatives - Sophy, K. B.; Shedge, Sapana V.; Pal, Sourav (Journal of Physical Chemistry A, 2008)
We report the effect of substitution, position of the substituent, and the symmetry on the nonlinear optical properties of p-nitroanline (PNA) and its derivatives using our implementation of the noniterative approximation of couple-perturbed Kohn-Sham (CPKS) equation in the deMon2k. Dipole moment, static polarizability, and first hyperpolarizability of these pi-conjugated donor-acceptor organic derivatives of PNA and its methyl-substituted analogs are calculated using our method at different exchange correlation functionals, namely, BP86, BPW91, and BLYP, using 6-31++G** basis set. A comparison of results obtained by our method with those obtained by MP2 (finite-field perturbation) method is presented in this paper. The effect of optical gap on charge transfer and subsequently on polarizabilities has been illustrated.